2015
DOI: 10.1049/el.2015.0428
|View full text |Cite
|
Sign up to set email alerts
|

Planar ultra‐wideband printed wide‐slot antenna using fork‐like tuning stub

Abstract: A printed wide-slot antenna with a centred rectangular parasitic patch, fed by a fork-like tuning stub with rectangular parasitic elements adjacent to the main feed line is proposed and discussed. The proposed wide-slot antenna eliminates the need of rotation of the slot and parasitic patches both in the ground plane for the improvement in impedance bandwidth. The experimental results indicate that the presented antenna has a bandwidth (−10 dB) of more than 148% ranging from 2 to 13.5 GHz. The total size of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…In [22], a printed elliptical slot antenna using a tapered microstrip feeding line with a fork-shaped tuning stub achieved an impedance BW of 117% for S 11 < −10 dB. In [23], a printed WS antenna with a centered rectangular parasitic patch, fed by a fork-like tuning stub with rectangular parasitic elements is proposed, with an impedance BW of 148.4% for S 11 < −10 dB. It has been demonstrated that designs using a fork-shaped stub are an effective way to obtain broadband impedance matching.…”
Section: Introductionmentioning
confidence: 99%
“…In [22], a printed elliptical slot antenna using a tapered microstrip feeding line with a fork-shaped tuning stub achieved an impedance BW of 117% for S 11 < −10 dB. In [23], a printed WS antenna with a centered rectangular parasitic patch, fed by a fork-like tuning stub with rectangular parasitic elements is proposed, with an impedance BW of 148.4% for S 11 < −10 dB. It has been demonstrated that designs using a fork-shaped stub are an effective way to obtain broadband impedance matching.…”
Section: Introductionmentioning
confidence: 99%
“…5 represents the comparison between the simulated and measured gain of the fabricated antenna. The gain is improved as compared to the reference antenna [11] for the frequency range of 1.8-6.1 GHz. The measured gain varies from 3.3-8.25 dB with a maximum value of 8.25 dB at 10.5 GHz.…”
Section: Resultsmentioning
confidence: 93%
“…Introducing a patch at the slot provides additional surface current path creating more resonance and improving the bandwidth [10]. In this paper, a slot antenna is proposed based on the work of [11]. Off-set feed line [12][13][14][15] is used to reduce the size of the antenna and to enhance the bandwidth further improvement in the bandwidth is observed by using dual SRR and semicircular slots in the ground plane.…”
Section: Introductionmentioning
confidence: 99%
“…UWB antenna has been widely used not only in military and civil wireless communication, but also in biomedical detection, because of its unique features such as broad impedance bandwidth and high speed data rate [2,3]. After the Federal Communication Commission (FCC) approved the opening of 3.1-10.6 GHz band to the business in 2002 [4], various kinds of UWB antennas have been studied and designed, such as Vivaldi antenna, printed monopole antenna, and wide slot antenna [5][6][7].…”
Section: Introductionmentioning
confidence: 99%